Impact of a Clinical Pharmacy Admission Medication Reconciliation Program on Medication Errors in "High-Risk" Patients. (December 2013) - Buckley, Mitchell S.; Harinstein, Lisa M.; Clark, Kimberly B.; Smithburger, Pamela L.; Eckhardt, Doug J.; Alexander, Earnest; Devabhakthuni, Sandeep; Westley, Craig A.; David, Butch; Kane-Gill, Sandra L.
Background: Medication errors are common upon hospital admission. Clinical pharmacist involvement in medication reconciliation is effective in identifying and rectifying medication errors. However, data is lacking on the economic impact, time requirements, and severity of errors resolved by clinical pharmacists.Objective: To determine the incidence of unintended admission medication discrepancies resolved by clinical pharmacists. Secondary objectives were to determine the type of discrepancies, potential severity, proximal cause, and economic impact of this clinical pharmacy program.Methods: This was a single-center, prospective, observational study conducted at a major teaching medical institution. Following institutional review board approval, data collection was conducted over a 4-week period (August 22, 2011, to September 16, 2011). Descriptive statistical methods were performed for all data analyses.Results: A total of 517 patients involving 5006 medications were included in this study. More than 25% (n = 132) of patients had at least 1 error associated with a medication ordered on hospital admission. Pharmacists resolved a total of 467 admission medication errors (3.5 ± 2.3 errors/patient). The most common type of medication error resolved was medication omission (79.6%). In regard to severity, 46% of medication errors were considered significant or serious. Overall, the mean total time was 44.4 ± 21.8 minutes per medication reconciliation. This clinical pharmacy program was estimated to carry a net present value of $5.7 million over 5 years.Conclusion: Clinical pharmacist involvement within a multidisciplinary health care team during the admission medication reconciliation process demonstrated a significant improvement in patient safety and an economic benefit.